PENGARUH KINERJA KEUANGAN PERUSAHAAN DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - admin, MILLA FITRIA B11112110 (Jurnal Manajemen Update, 2016)
The firm’s value has become one of the firm’s objectives, as it becomes the firm’s framework in managing the company. The main purpose of the firm’s value in the long term is to increase the prosperity of the shareholders. This study aims to scrutinize the impact of financial performance and coorporate social responsibility disclosure on the firm’s value in the firms of consumer goods listed on Indonesian Stock Exchange.   The method of this study uses the quantitative research, the type of data used in this study is the secondary data which has been collected by data gathering institutions and published to the data users in the society. The sample of this study is taken by using purposive sampling. The firms used as the sample are the firms of consumer goods listed in  Indonesian Stock Exchange index during the period of 2012 – 2014. The sample selection is based on the development of the Return On Asset, Debt To Equity Ratio, Cash Conversion Cycle, Corporate Social Responsibility, as well as Tobins Q. After the selection, the writer obtains the total sample of 24 firms which are able to fulfill the criterions as the sample. In the analysis of the data multiple regression analysis is used to determine the effect of the variables involved in this study, with application tool of SPSS  (Statistical Product and Service Solutions). The results showed that profitability is only significant positive Return On Asset and Corporate Social Responsibility to the value of the company. This means that high Return On Asset and Corporate Social Responsibility can provide added value to the company, which is reflected by the increasing value of Tobins Q. Keyword : corporate financial performance, corporate social responsibility disclosure, firm’s value